A transição energética justa e a sua incompatibilidade com as disposições sobre investimento da Energy Charter Treaty: o diálogo necessário com o Pacto Verde Europeu - Mata, Antônio Lucas dos Santos da (2024)
The fight against climate change requires the adoption of transition strategies towards globally emissions-neutral systems, especially affecting sectors most responsible for greenhouse gas (GHG) emissions. Currently, one of the sectors targeted for transition is the energy sector, notably due to the excessive use of fossil fuels. In fact, at the most recent Conference of the Parties (COP) of the United Nations Framework Convention on Climate Change (UNFCCC), it was adopted a decisions that was considered the starting point to end the era of fossil fuels in favour of promoting renewable energy sources. Both internationally and nationally, various strategies have been adopted to meet the climate goals of the Paris Agreement and achieve climate neutrality by 2050. This includes measures taken in the European Union (EU) within the context of the European Green Deal (EGD). One of the EU's focuses is breaking the dependence on fossil fuels, a process accelerated due to the war between Russia and Ukraine. However, despite the ambitious goals of the EU regarding energy transition, there are still barriers in the international investment law, such as the Energy Charter Treaty (ECT), which poses a risk to the adoption of more daring regulatory measures. In this sense, this dissertation aims to discuss the compatibility between the original and “modernised” provisions of the ECT with the new objectives and values of the EU, especially those present in the EGD regarding the just energy transition, including provisions on sustainability and human rights. The methodology adopted is based on bibliographical and documentary analysis, reviewing literature such as articles, reports, books, among others, related to the analysed theme. It also involves investigating documents, both national and international, related to the ECT and the EGD. In conclusion, it can be stated that the original provisions and the attempt to modernize the ECT are not compatible with the contemporary paradigms of the EU and pose a risk to the evolutionary process of energy transition. Therefore, the maintenance of the ECT and its member states as signatories to this treaty should be reevaluated.